Case Report: Nutrition profile, body mass, sleep quality, and acute mountain sickness symptoms during altitude training in a Paralympic record-breaking athlete and his two guides - Belluco, Kimberly; Breda, Fabio Leandro; Lourenço, Thiago Fernando; Cirino, Carolina; Papoti, Marcelo; Gobatto, Claudio Alexandre; Manchado-Gobatto, Fúlvia Barros (Frontiers in Nutrition, 2025)
Altitude training under the “live high-train high” regime is commonly used by athletes to enhance sea-level performance. However, careful monitoring is required, since nutritional aspects, sleep quality, and acclimatization symptoms may influence results and pose health risks. This is especially relevant in elite athletes aiming for peak performance. The aim of this case study was to assess the nutritional profile, body mass, sleep quality, and mountain sickness symptoms of a Paralympic athletics world record holder in the T11 class (1A), three-time world record holder, and his two guides (2G and 3G), with weekly measurements during the altitude training period. The athletes underwent 30 days of training in Colombia, in a city located approximately 2,150 meters above sea level. At baseline and during each training week, body weight, a food recall, and symptoms of Acute Mountain Sickness (AMS) were collected using the Lake Louise Symptom Score. Sleep quality was analyzed twice, before and after training, using the Epworth scale (ESS) and the Pittsburgh questionnaire (PSQI). No major changes were observed in body mass (1A: 1.52%; 2G: −2.67%; 3G: 0.16%) or sleep quality, which remained stable across both assessments. On the ESS, 2G showed scores indicative of excessive daytime sleepiness, while on the PSQI, 3G demonstrated suboptimal sleep quality; values did not change pre- to post-altitude. Mild AMS was reported by 1A and 2G on day 1 (scores 3–5), whereas 3G showed no symptoms. Appetite remained stable, but carbohydrate intake (1A: 4.8–5.7 g·kg−1·day−1; 2G: 3.8–5.9 g·kg−1·day−1; 3G: 4.4–5.4 g·kg−1·day−1) was below American College of Sports Medicine (ACSM) recommendations. These findings underscore the importance of systematically monitoring nutrition, body mass, sleep quality, and AMS symptoms during altitude training, providing practical guidance for coaches and supporting optimal preparation of Paralympic athletes.